Tailored microstructure of colloidal lipid particles for Pickering emulsions with tunable properties. Issue 17 (11th April 2017) - Schröder, Anja; Sprakel, Joris; Schroën, Karin; Berton-Carabin, Claire C.
Abstract : Sub-micron colloidal lipid particles (CLPs) can successfully be used as Pickering stabilizers in oil-in-water (O/W) emulsions, leading to enhanced stability compared to conventional emulsifier-stabilized emulsions. Abstract : Sub-micron colloidal lipid particles (CLPs) can successfully be used as Pickering stabilizers in oil-in-water (O/W) emulsions, leading to an enhanced physical stability compared to conventional emulsifier-stabilized emulsions. Varying the lipid solid–liquid ratio leads to particles with distinct nanostructure and morphology, resulting in tunable emulsion stabilization performance. Our CLPs are produced by hot high pressure homogenization of high melting point fats in water, and subsequent cooling to induce lipid crystallization. Lath-like tripalmitin and palm stearin CLPs form jammed, cohesive interfacial layers that prevent relaxation of emulsion droplets, and form a three-dimensional network in the continuous aqueous phase. CLPs consisting of a mixture of solid tripalmitin and liquid tricaprylin are polycrystalline platelet-like particles that form O/W emulsions with spherical and bridged droplets covered by a thin particle layer. Our results present a versatile approach to interfacial design that also opens up new perspectives for development of novel delivery systems for active ingredients.